Blood Flow Simulation Using Traceless Variant of Johnson-Segalman Viscoelastic Model. (24th September 2014) - Sequeira, A.; Volpert, V.; Bodnár, T.; Pires, M.; Janela, J.
<x content-type="archive" xml:space="preserve">Abstract</x> A traceless variant of the Johnson-Segalman viscoelastic model is presented and applied to blood flow simulations. The viscoelastic extra stress tensor is decomposed into its traceless (deviatoric) and spherical parts, leading to a reformulation of the classical Johnson-Segalman model. The equivalence of the two models is established comparing model predictions for simple test cases. The new model is validated using several 2D benchmark problems, designed to reproduce difficulties that arise in the simulation of blood flow in blood vessels or medical devices. The structure and behaviour of the new model are discussed and the future use of the new model in envisioned, both on the theoretical and numerical perspectives.